Bloodstream Infection Following Cardiac Valve Repair: A Population-Based Study. (18th November 2021) - McHugh, Jack W; Talha, Khawaja M; Baddour, Larry M; Fischer, Karen M; Crestanello, Juan; Arghami, Arman; DeSimone, Daniel C
Abstract: Background: The aim of this study was to determine the incidence, epidemiology, and associated risk factors of bloodstream infection (BSI) in patients who had previously undergone cardiac valve repair. Methods: A population-based study that included 7 counties in southeastern Minnesota using the expanded Rochester Epidemiology Project (e-REP) for adults (≥18 years) who underwent valve repair between 1 January 2010 and 31 December 2018 was conducted. Electronic health records were screened for development of BSI and infective endocarditis (IE) from the date of valve repair through 30 July 2020. A 1:4 nested case-control analysis was performed to determine an association, if any, of male sex, Charlson comorbidity index (CCI), and county of residence with BSI. Results: A total of 335 patients underwent valve repair, of whom 28 (8.3%) developed an index case of BSI, with 14 episodes occurring within 1 year of surgery. The median age of patients with BSI was 70 years, and 79% were male. The crude incidence of BSI was 1671 cases per 100000 person-years and Escherichia coli was the most common pathogen. Case-control analysis demonstrated a significant correlation between CCI and incidence of BSI ( P < .001). Only 4 (14.3%) patients developed IE concurrent with the onset of BSI, and no patients developed IE subsequent to BSI. Conclusions: The crude incidence of BSI following valve repair was higher in our e-REP cohort than previous population-based studies, and half of the BSI cases occurred within 1 year of surgery. Patients with a higher CCI at baseline were at increased risk of subsequent BSI.